Prostaglandin E2 mediates sensory nerve regulation of bone homeostasis - Hao Chen (Nature Portfolio, 2019)
Bone is innervated, and its turnover is affected by sympathetic nerve activity. Here, the authors show that prostaglandin E2, secreted by osteoblasts, activates the EP4 receptor on sensory nerves, inhibiting sympathetic nerve activity and modulating bone formation in mice.